Welsh Borderland bouillabaisse: Lower Old Red Sandstone fish microfossils and their significance. Issue 3 (June 2017) - Turner, Susan; Burrow, Carole J.; Williams, Rod B.; Tarrant, Peter
Abstract: Fish remains from over 100 localities in the Upper Silurian to Lower Devonian (traditional Lower Old Red Sandstone: LORS: Přidolí–Pragian) of Wales and the Welsh Borderland Anglo-Welsh Basin, southwest Britain have been investigated. Work on microfossils of fish ('microvertebrates', generally <5–8 mm) is reviewed, covering agnathan thelodonts, heterostracans, cephalaspids, anaspids, and gnathostomes including acanthodians, placoderms, and chondrichthyans, including the first from Pembrokeshire. Scales of the following taxa are newly identified: acanthodians Euthacanthus sp., Nostolepis musca, Parexus recurvus and Cheiracanthoides sp. cf. C. rarus ; early "sharks" including Altholepis sp.; and a (?)radotinid placoderm. Species ranges in space, time and environment reveal interesting patterns, the most significant being a wide geographic distribution, which does not support a wholly freshwater provenance for the Anglo-Welsh Basin; endemic taxa are few. Using the International mid-Palaeozoic Microvertebrate zonal scheme, the presence of a Thelodus parvidens – Paralogania ludlowiensis -osteostracan Assemblage within the Ludlow Bonebed at the base of the former Downton Group (now in part in the new lithostratigraphically defined Daugleddau Group) supports a basal Přidolí age for the member. A mid-Přidolí dearth with few taxa, mainly acanthodians and cephalaspids is followed by an upper Přidolí Trimerolepis – Paralogania kummerowi – Loganellia cuneata -poracanthodid- Toombsaspis pococki Assemblage. The Silurian–Devonian boundary is equated with the appearance of Turinia pagei and associated taxa including Phialaspis symondsi at a level about 30 m below the local Chapel Point Limestone. This biozone can be correlated across the Old Red Sandstone continent. All vertebrate species including newly recognised Lochkovian chondrichthyans indicate marine environments were present in the LORS.